2018
DOI: 10.4102/jef.v11i1.175
|View full text |Cite
|
Sign up to set email alerts
|

Investigating a new wealth tax in South Africa: Lessons from international experience

Abstract: In recent years, there has been an increasing focus on new sources of taxation, including wealth tax. In South Africa, two phenomena have driven the focus on wealth tax. Firstly, the need for additional tax revenue to fund an ongoing and growing budget deficit, exacerbated by a prolonged period of low economic growth, rising government debt and a very small base of individual taxpayers. Secondly, the fact that South Africa has one of the most unequal societies in the world. The dual demands of increased tax re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Through turning public enterprises profitable, revenue can be employed to invest in public-private ventures to increase labour market absorption. These results are similar to the findings of Lentz and Tranaes (2005), Dickens et al (2017), Arendse and Stack (2018), Padayachee (2019), andBond andMalikane (2019).…”
Section: Discussionsupporting
confidence: 92%
“…Through turning public enterprises profitable, revenue can be employed to invest in public-private ventures to increase labour market absorption. These results are similar to the findings of Lentz and Tranaes (2005), Dickens et al (2017), Arendse and Stack (2018), Padayachee (2019), andBond andMalikane (2019).…”
Section: Discussionsupporting
confidence: 92%
“…According to latest available data from the World Bank, the Gini index in South Africa was at 63 in 2014, the largest among 83 countries with an estimated Gini index 1 . While historically, most studies have focused on describing and analysing income inequality (Leibbrandt et al, 2012), wealth inequality and its pervasiveness in the South African society has come under scrutiny only very recently and as part of a broader debate over government fiscal policies in response to historic inequalities and recent COVID-19 related economic hardship (Arendse and Stack, 2018;Chatterjee et al, 2021). Using historical records of tax micro data, household surveys, and macroeconomic balance sheet statistics, it has been shown that the top 10 per cent own 86 per cent of aggregate wealth in South Africa and such high levels of inequality in wealth distribution has stayed unchanged since the transition from apartheid to democracy (Chatterjee et al, 2020).…”
Section: Wealth Inequality In South Africamentioning
confidence: 99%
“…Using historical records of tax micro data, household surveys, and macroeconomic balance sheet statistics, it has been shown that the top 10 per cent own 86 per cent of aggregate wealth in South Africa and such high levels of inequality in wealth distribution has stayed unchanged since the transition from apartheid to democracy (Chatterjee et al, 2020). Some studies have suggested that imposing a wealth tax could address underlying economic inequality and tax deficits to some degree (Arendse and Stack, 2018). However, the feasibility and effectiveness of such policy proposals highly depend on the future socioeconomic and political development in South Africa which will directly impact the wealth creation, accumulation and…”
Section: Wealth Inequality In South Africamentioning
confidence: 99%